Process simulation of hydrogen production from bio-oil using iCON - Ahmad, M.M. (Taylor and Francis Inc., 2016)
This work aims to investigate the feasibility of upgrading bio-oil into hydrogen via steam reforming and water shift reactions using conceptual design and simulation approaches. In the simulation work using PETRONAS iCON software, it is assumed that the aqueous fraction of bio-oil comprises of 67 acetic acid, 16.5 acetone, and 16.5 ethylene glycol. It is observed that increment in temperature and the amount of steam supplied in the steam reformer increase the hydrogen production until a certain extent. Meanwhile, opposite effect on hydrogen production is observed for both the temperature and steam used in the shift reactor. The overall conversion predicted for the process is 84 at operating temperatures and pressures for the steam reformer and shift reactor of 650 and 200Â°C, and 1 and 17 bar, respectively, and at the molar steam-to-carbon ratio (S:C) of 6.5. The results are compared and showed good agreement with those from published simulation and experimental work. Positive preliminary economic potential was obtained for the process developed, that is, USD 5.56 Ã 106/year. Â© 2016 Taylor & Francis Group, LLC.